Vision based robot positioning and recognition using artificial intelligent system - Fathinul-Syahir, Ahmad Sa'ad; Hazry, Desa, Dr.; Muhammad Juhairi Aziz, Safar; Md Tasyrif, Abdul Rahman (International Islamic University Malaysia (UIAM), 2011)
Organized by International Islamic University Malaysia (UIAM), 18th - 20th December 2008 at Kuala Lumpur, Malaysia.